The Principal’s Leadership in Developing the Religious Values in SMA Negeri 1 Jatiroto - Slamet Priyanto; Usman Zainuddin Urif; Wahyu Kurnia Utami (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2019)
The values of religion in SMANJA recently is described as a school community which hasn’t applied the values of religious (optimally/maximally) in daily life. The school life has not given the life based on the religious values taught by islam. The headmaster is trying to motivate all the school citizen to create/ develop the religious values and try to implement the values at school maximally. In daily life, most of school citizen do implement the religious values at school, for example: a) The activity of praying dzuhur and ashar, b) The activity of prayer Dhuha are not maximally implemented. The goal of this research is to reveal the principal’s leadership of developing the religious values in SMANJA. 1. Describing the religious values which are implemented in school community. 2. Describing the role and the effort of the principal in developing the religious values. 3. Describing the response of school citien in the offense of developing the religious values. This research applies the qualitative research approach. The sources of the research are the school principal, the vice principal, the teachers, the TU staff, OSIS committee and Remush, while the data collecting methodology is done by observation, and documentation. The results of the research are analyzed by data reduction, data display and data verification. The result of the research on the leadership in developing the religious values principal in SMAN Jatiroto including: 1. A calling for praying dhuhurwhichis done by the OSIS committee’s member in turn. 2. Holding the Dhuhur/Ashar praying. 3. Celebrating the Islamic Religion Day. 4. Holding the examination DO’A together with students of XII grade and their parents face the national and school